LightCDD: Application of a Capability-Driven Development Method for Start-ups Development - Hasan Koç; Marcela Ruiz; Sergio España (Complex Systems Informatics and Modeling Quarterly)
Novice innovators and entrepreneurs face the risk of designing naive business models. In fact, lack of viability in business models is perceived to be a major threat for the start-up success. Both the literature and the responses we gathered from experts in incubation present evidences of this problem. The LightCDD method helps entrepreneurs in the analysis, design and specification of start-ups that are context aware and adaptive to contextual changes and evolution. In this article we describe the LightCDD method, a context-aware enterprise modeling method that is tailored for business model generation. The LightCDD applies a lightweight Capability‑Driven Development (CDD) methodology. It reduces the set of modeling constructs and guidelines to facilitate its adoption by entrepreneurs, yet keeping it expressive enough for their purposes and, at the same time, compatible with the CDD methodology. We provide a booklet with the LightCDD method for start-ups development. The feasibility of the LightCDD method is validated by means of its application to one start-up development case. From a practitioner viewpoint (entrepreneurs and experts in incubation), it is important to provide integrative modeling perspectives to specify business ideas, but it is vital to keep it light. The LightCDD is giving a step forward in this direction. From a researcher point of view, the LightCDD booklet facilitates the application of LightCDD to different start-up development cases. The feasibility validation has produced important feedback for further empirical validation exercises in which is necessary to study the scalability and sensitivity of LightCDD.